Educating School Teachers - Levine, Arthur (The Education Schools Project, 2006)
Contents include: Teacher Education in Flux, The Pursuit of Irrelevance, Inadequate Preparation, A Curriculum in Disarray, A Disconnected Faculty, Low Admission Standards, Insufficient Quality Control, Disparities in Institutional Quality, Exemplary Teacher Education Programs, Educating the Teachers America Needs, and five Appendixes.